HOSPICE CARE FOR STROKE PATIENTS: ANALYSIS OF ISSUES AND CHALLENGES IN THE HOSPICE CARE MODEL FOR CHRONIC STROKE PATIENTS - Ismail, Faisal Husen; Husain, Mohd Huefiros Efizi; Sahimi, Mohd Shafiq; Arwansyah Kirin, Arwansyah Kirin; Mohammad, Che Adenan; Rashid Ali, Mohamad Shahrudin (rgsa, 2024)
Background: The lives of stroke patients are often marked by changes in function and cognition that alter their lives, along with exacerbating symptoms. Hospice care emphasizes quality care that focuses on improving patient comfort, reducing pain, and providing emotional support to patients and their families. Objective: This study aims to discuss the hospice care model for chronic stroke patients. Method: The research methodology is conducted qualitatively through a literature review method, referring to printed materials such as journals, newspapers, magazines, and relevant books to elucidate the hospice care model and elements related to the care of chronic stroke patients. This article analyzes data from documents and selected texts, followed by a thematic coding process. Result: The study finds that the hospice care model has become an increasingly popular alternative in providing comprehensive and holistic care for chronic stroke patients. However, the implemented hospice care model has its own limitations and challenges. Conclusion: Overall, this article will provide a deeper understanding of the hospice care model for chronic stroke patients. A precise understanding of this model's provision will enhance the quality of hospice care for chronic stroke patients and improve overall well-being. Nursing Implications: The importance of this study lies in gaining a deeper understanding of the effectiveness of the hospice care model for chronic stroke patients and enhancing the provision of quality care for them. By understanding existing models and assessing strengths and weaknesses, we can identify aspects that need improvement in providing better and more appropriate care.